Green Chemical Processes : Developments in Research and Education - Andino Martinez, Jose G.; Benvenuto, Mark Anthony; Bodner, George M.; Consiglio, David; Desmond, Serenity; Kolopajlo, Larry; Kosmas, Steven; Pharr, Daniel Y.; Ray, Christian; Stevens, Jonathan (Green Chemical Processing, 2017)
The "greening" of industry processes - i.e., making them more sustainable - is a popular and often lucrative trend which has seen increased attention in recent years. Green Chemical Processes, the 2nd volume of Green Chemical Processing, covers the hot topic of sustainability in chemistry with a view to education, as well as considering corporate and environmental interests, e.g. in the context of energy production. The diverse team of authors allows for a balance between these different, but interconnected perspectives. The American Chemical Society's 12 Principles of Green Chemistry are woven throughout this text as well as the series to which this book belongs.